2006
DOI: 10.3349/ymj.2006.47.6.787
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Polymorphisms of the Dopamine Receptor D4 and Dopamine Transporter Genes and Personality Traits in a Korean Population

Abstract: Human personality traits have a considerable genetic component. Cloninger et al. were the first to postulate that certain personality traits, such as novelty seeking, are related to the dopamine neurotransmitter system. In this study, we investigated the associations between dopamine receptor D4 (DRD4) exon III and dopamine transporter (DAT1) polymorphisms and personality traits. The DRD4 and DAT1 gene polymorphisms were genotyped in 214 healthy Korean subjects, whose personality traits were assessed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…However, our present study of total, male or female subjects identified no significant association between any of the 3 tested SNPs in the NTR1 gene, which is closely connected to the dopamine system, and NS scores, suggesting that NTR1 is not a defining factor in the NS temperament dimension, at least in the Chinese Han genetic background. In fact, the current results are consistent with those of many previous studies that found no associations between DRD2 [44], DRD4 [44,45,46,47,48], and dopamine transporter 1 [47] gene variants and NS in different healthy populations, and that did not replicate the results that variants in the genes encoding proteins in the dopamine system were related to NS trait scores.…”
Section: Discussionsupporting
confidence: 81%
“…However, our present study of total, male or female subjects identified no significant association between any of the 3 tested SNPs in the NTR1 gene, which is closely connected to the dopamine system, and NS scores, suggesting that NTR1 is not a defining factor in the NS temperament dimension, at least in the Chinese Han genetic background. In fact, the current results are consistent with those of many previous studies that found no associations between DRD2 [44], DRD4 [44,45,46,47,48], and dopamine transporter 1 [47] gene variants and NS in different healthy populations, and that did not replicate the results that variants in the genes encoding proteins in the dopamine system were related to NS trait scores.…”
Section: Discussionsupporting
confidence: 81%
“…However, one study implies that an A/G SNP in the 10 allele may be associated with vulnerability to alcoholism [136]. To a lesser extent other associations with this VNTR have been examined but most find no correlation, these include; body weight, body mass index or obesity [137], Tourette's [138], personality traits (novelty seeking, harm avoidance, reward dependence and persistence [139]), cocaine dependence [140]; and schizophrenia [141].…”
Section: -Htt Variants and Anti-depressant Efficacymentioning
confidence: 98%
“…For mer stu di es re ve a led conf lic ting results on DRD4 or 5-HT2A poly morp hisms and novelty se e king. In so me stu di es, no velty se e king was shown to be re la ted with DRD4 poly morpTurkiye Klinikleri J Med Sci 2010;30 (5) [19][20][21] Se veral stu di es ob ser ved as so ci a ti ons bet we en 5-HT2A and no velty se e king. 22 In con trast, some stu di es reve a led that 5-HT2A was ne ga ti vely re la ted with cons ci en ti o us ness 23 and po si ti vely cor re la ted with ne u ro ti cism (emo ti o nal sta bi lity).…”
Section: Discussionmentioning
confidence: 99%